Answer:
= 3
Step-by-step explanation:
Add 6 to both sides of the equation 10 − 6 = 6 + 6
10x-6=6x+6 10x−6=6x+6
Simplify Add the numbers Add the numbers again 10 = 6 + 12
Subtract 6 from both sides of the equation
10 = 6 + 12
10−6=6+12−6
Simplify
Combine like terms
Combine like terms again
4 = 12
Divide both sides of the equation by the same term
4=12
[tex]\frac{4x}{4}[/tex] =[tex]\frac{12}{4}[/tex]
Simplify Cancel terms that are in both the numerator and denominator then Divide the numbers.
x = 3